SWOT Strategy Analysis of the Robusta Coffee Processing Business of the Air Lanang Coffee MSME in Rejang Lebong Regency - Aulia, Maranggi; Wakarandi , Rolinly; Sudarma , Rahmad; Arborea , Alvira Dewi; Reflis, Reflis; Lestari, Fitri (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
This study aims to analyze internal and external factors influencing the development of Air Lanang Coffee's MSMEs and formulate appropriate strategies through a SWOT analysis approach. The research method used a qualitative approach with a purposive sampling technique, in which MSME owners were selected as the main respondents. Data were collected through interviews, observations, and document reviews. The results showed that MSMEs have strengths in the form of full control of the production process, adequate equipment facilities, and access to quality raw materials from local farmers. Weaknesses found include limited product diversification, unstable raw material quality, and low digital promotion. External opportunities include increasing coffee consumption, the development of digital marketing, partnerships with farmers, and the potential for coffee educational tourism. Meanwhile, threats come from coffee price fluctuations, MSME competition, quality regulations, and changes in consumer preferences. The SWOT analysis resulted in development strategies based on SO, WO, ST, and WT that can be directed to increase MSME competitiveness. Keywords: Coffee MSME, SWOT Analysis, Development Strategy, Air Lanang Coffee